PENGEMBANGAN SISTEM INFORMASI JASA PENUKARAN VALAS - Perbangsa, Anzaludin Samsinga; Reyner, Aloysius; Nugroho, Joshua Christian; J, Junne (Infotech: Journal of Technology Information, 2019)
The role of money changers is very important in meeting the needs of foreign exchange for the community. This role can also be fulfilled by banks and other financial institutions. People who want to order foreign currencies at this time still have to go through traditional procedures, where the buyer is required to come directly to the place of foreign exchange. This study intends to build a system design that can make currency orders and provide information on foreign exchange rates contained in each money changer through a web-based application. This research uses the Object Oriented Analysis and Design (OOAD) method, literature study, and data collection methods using a questionnaire. Based on the problems outlined and the results of the study, this system can be a source of information on foreign exchange rates and also an alternative order for foreign exchange. Foreign exchange orders can be made online through this information system. This system will continue to be developed with various features such as payment methods using biometric security methods with the support of Artificial Intelligence (AI) technology. So users can search for foreign currency values and order them easily through online media.